KINERJA GURU SMK NEGERI 1 SUKOHARJO DITINJAU DARI REMUNERASI, KETAATAN PERATURAN, DAN MOTIVASI - Listiana Muji Rahayu; Supawi Pawenang; Kartika Hendra Titisari (JURNAL ILMIAH EDUNOMIKA, 2020)
The research purpose was determined the effect of renumeration, obedience to the rules, and motivation to the performance of teachers of SMK Negeri 1 Sukoharjo. The research type is explanatory research. The research population are teacher of SMK Negeri 1 Sukoharjo. Sampling technique was used purposive sampling technique. Data collection was used questionnaires. Data analysis techniques were used statistical analysis including of multiple linear tests, F-test, and t-test. The research results showed that 1) remuneration has significant effect to the performance of teacher of SMK Negeri 1 Sukoharjo; 2) obedience to the rules has no significant effect to the performance of teacher of SMK Negeri 1 Sukoharjo; 3) motivation has significant effect to the performance of teacher of SMK Negeri 1 Sukoharjo; 4) remuneration, obedience to the rules, and motivation simultaneously has significant effect to the performance of teacher of SMK Negeri 1 Sukoharjo. Keywords: renumeration, obedience to the rules, motivation, performance